TEACHING VISUALIZATION TECHNOLOGIES AS A FACTOR IN THE DEVELOPMENT OF DIGITAL COMPETENCE OF FUTURE COMPUTER SCIENCE TEACHERS - Bakytbekova Ж.Б.; Kamalova Г.Б. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2024)
The research is devoted to the analysis of the impact of teaching modern technologies of visualization of educational information on the development of digital competence of future computer science teachers. In the context of the digital transformation of the educational process, emphasized in the strategic programs of the Republic of Kazakhstan, the study emphasizes the importance of integrating innovative didactic approaches and digital technologies into the system of training future teachers. Analyzing the survey data of 115 respondents and comparing the self-assessment of knowledge of future and practicing computer science teachers on various aspects of educational information visualization technologies, the study reveals differences in their digital competence and emphasizes the need for practical interaction with such technologies to fully unlock their potential, understand their capabilities and effectively use them in the educational process.